2009
DOI: 10.1590/s0104-42302009000500018
|View full text |Cite
|
Sign up to set email alerts
|

Comparação do ultrassom transvaginal e da histeroscopia ambulatorial no diagnóstico das doenças endometriais em mulheres menopausadas

Abstract: Objective.To compare the effectiveness of transvaginal ultrasound and outpatient diagnostic hysteroscopy in the diagnosis of intrauterine diseases in postmenopausal women. MethOds. The sample consisted of 243 postmenopausal women who submitted to diagnostic hysteroscopy in the year of 2006. All the women were referred from primary healthcare units after submitting to transvaginal ultrasound to assess the endometrial cavity. Results. The mean age of women was 61±9.4 years, and the mean time since entering menop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Similar to the findings in this study, Mukhopadhayay et al found a high sensitivity (71.4%) and specificity (100.0%) for hysteroscopy for diagnosing polyps [14] with strong agreement with biopsy findings (k=0.81). Soguktas et al found better diagnostic value for hysteroscopy when compared to both saline infusion sonography and transvaginal ultrasonography in detecting uterine polyps; however, for detection of any uterine pathology, hysteroscopy and saline infusion sonography had similar efficacy but better than transvaginal ultrasonography [15] Similarly, Mathlouthi et al [16] and Yela et al [17] found diagnostic values in favor of hysteroscopy for the diagnosis of uterine pathologies. In the study by Yela et al, the specificity of TVU in particular was remarkably low (7.4%) for the detection of uterine disease [17] Kasraeian et al, examined the diagnostic value of transvaginal ultrasonography in non-bleeding postmenopausal women and found only moderate accuracy to diagnose uterine pathologies [18].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings in this study, Mukhopadhayay et al found a high sensitivity (71.4%) and specificity (100.0%) for hysteroscopy for diagnosing polyps [14] with strong agreement with biopsy findings (k=0.81). Soguktas et al found better diagnostic value for hysteroscopy when compared to both saline infusion sonography and transvaginal ultrasonography in detecting uterine polyps; however, for detection of any uterine pathology, hysteroscopy and saline infusion sonography had similar efficacy but better than transvaginal ultrasonography [15] Similarly, Mathlouthi et al [16] and Yela et al [17] found diagnostic values in favor of hysteroscopy for the diagnosis of uterine pathologies. In the study by Yela et al, the specificity of TVU in particular was remarkably low (7.4%) for the detection of uterine disease [17] Kasraeian et al, examined the diagnostic value of transvaginal ultrasonography in non-bleeding postmenopausal women and found only moderate accuracy to diagnose uterine pathologies [18].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike premenopause women, many studies have studied the accuracy of TVS in diagnosing endometrial abnormalities especially EH among postmenopause women and has become an essential screening in gynecological practice in these women. 11 14 26 However, different studies have yielded different levels of sensitivity and specificity ranging from 59.7%–100% to 7.4%–91.7%, respectively. 14 20 27 28 29 30 31 32 In this study, we observed a high accuracy for TVS in diagnosing EH in postmenopause women with sensitivity, specificity, PPV and NPV of 100% for each.…”
Section: Discussionmentioning
confidence: 99%
“… 11 14 26 However, different studies have yielded different levels of sensitivity and specificity ranging from 59.7%–100% to 7.4%–91.7%, respectively. 14 20 27 28 29 30 31 32 In this study, we observed a high accuracy for TVS in diagnosing EH in postmenopause women with sensitivity, specificity, PPV and NPV of 100% for each. Similarly, a high NPV (99%) is reported for TVS in untreated postmenopausal women, 16 33 but there is reported poor NPV in some studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Submucous myomas of the uterus, which mainly show spherical or hemispherical structures and protrude in the uterine cavity, are mostly characterized by a wide base, hypoechoic or isoechoic, and swing without the influence of contrast agents [ 13 ]. The uterine cavity was deformed, and some endometrial hyperechoic lines could be seen entangled on the surface of the fibroid protrusion, with a smooth front and disappearance of endometrial hyperechoic lines at the base [ 14 ]. Hysteroscopy is an emerging field that appears in the field of modern gynecology, and it is a product combining electro-optic, ultrasound, and medical treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%